Sounds of a New Generation : On Contemporary Jewish-American Literature - Wallrabenstein, Deborah (Bielefeld : transcript-Verlag, 2017)
This book offers insight into the approaches of a new generation of Jewish-American writers. Whether they reimagine their ancestors' "shtetl life" or invent their own kind of Jewishness, they have a common curiosity in what makes them Jewish. Is it because most of them are third-generation Americans who don't worry about assimilation as their parents' generation did? If so, how does the writing of recent Jewish immigrants from the former Soviet Union fit into the picture? Unlike Irving Howe predicted in 1977, Jewish-American literature did not fade after immigration. It always finds new paths, drawing from the vast scope of Jewish life in America.
Frontmatter -- Content -- Acknowledgment -- Introduction -- 1. Generations on the Move -- 2. Contemporary Jewish-American Literature -- 3. The Past of Shtetl and Family -- 4. New Beginnings -- 5. The New 'Russian-Jewish-American' Literature -- Conclusion -- Bibliography
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 16. Mai 2019)
Keywords: American literature -- Jewish authors -- 20th century -- History and criticism; American literature -- Jewish authors -- 21st century -- History and criticism; America; American Studies; General Literature Studies; Jewish American Culture; Jewish American Literature; Jewish Immigration; Jewish Studies; Judaism; Literary Studies; Literature; Russian Jewish American; Juden; Literatur; LITERARY CRITICISM / American / General